1987
DOI: 10.1002/ajim.4700110505
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and respiratory symptoms in subjects with asbestos‐related disorders: A cross‐sectional study

Abstract: The prevalence of respiratory symptoms and lung function impairment was studied in a sample of men from a population screening of asbestos-related disorders. When the rates were adjusted for age and smoking habits, 83 subjects with lung fibrosis had an increased prevalence of respiratory symptoms, in particular, phlegm when coughing and breathlessness grades 1-3. Among 200 subjects under 70 years of age who had pleural plaques only, a statistically significant increase was observed in the prevalence of breathl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…They found that there was a significant association between angina pain and the presence of pleural and parenchymal abnormalities. Another exception was reported by Hilt et al (1987) who studied a cohort of asbestos exposed persons and found that among 200 subjects less than 70 years of age who had pleural plaques only, a statistically significant increase was observed in the prevalence of breathlessness grade 1 (light) after adjustment for smoking compared to an external reference population. The most recent study that addresses chest pain in asbestos exposed workers with pleural plaques is that of Park et al (2011).…”
Section: Pleural Plaques and Respiratory Symptomsmentioning
confidence: 90%
See 1 more Smart Citation
“…They found that there was a significant association between angina pain and the presence of pleural and parenchymal abnormalities. Another exception was reported by Hilt et al (1987) who studied a cohort of asbestos exposed persons and found that among 200 subjects less than 70 years of age who had pleural plaques only, a statistically significant increase was observed in the prevalence of breathlessness grade 1 (light) after adjustment for smoking compared to an external reference population. The most recent study that addresses chest pain in asbestos exposed workers with pleural plaques is that of Park et al (2011).…”
Section: Pleural Plaques and Respiratory Symptomsmentioning
confidence: 90%
“…With very few exceptions (Cramond & Casserly, 2006;Hilt et al, 1987;Mukherjee et al, 2000;Myers, 2012) investigators have concluded that most subjects with pleural plaques are nearly always asymptomatic (Ameille & Letourneux, 1999;Broderick et al, 1992;Christen et al, 1997;Crane et al, 2005;Crapo, 2005;Dweik & Mazzone, 2010;Fishwick & Barber, 2014;Hillerdal, 1997Hillerdal, , 2001Hillerdal & Henderson, 1997;IIAC, 2008;Järvholm & Larsson, 1988;Jones, 1997;Meirelles et al, 2005;Mohr, 2012;Montes et al, 2005;Park et al, 2011;Roach et al, 2002;Rubin, 1986;Utell & Maxim, 2010). For example: Broderick et al (1992) studied an asbestos exposed population of sheet metal workers and examined the relationship between circumscribed plaque and four symptoms; dyspnea upon hurrying or walking up a slight hill (DOE), dyspnea worse than peers while walking (DSP), chest pain and cough.…”
Section: Pleural Plaques and Respiratory Symptomsmentioning
confidence: 99%
“…An increased prevalence of pleural plaque formation has been observed in asbestos-e xposed populations (1)(2)(3)(4)(5)(6). While asbestos exposure has declined in recent decades the prevalence of pleural plaques appears to be rising, especially among males and older age groups (7).…”
mentioning
confidence: 99%
“…The heavy smokers in all the exposure groups had FVC and FEVl.o predicted values that were lower than those of the nonsmokers-light smokers; these differences remained constant with length of employment. Cessation of asbestos exposure for about 10 years did not seem to change lung function decline.Key terms: asbestos and smoking interaction, asbestos exposure, lung function after cessation of asbestos exposure, lung function change, total dust concentration.The effect of asbestos exposure on lung function has been reported in several cross-sectional (10,12,(17)(18)(19) 22) and a few longitudinal (2, 11,13,20,21) studies. The latter have usually been based on two surveys.…”
mentioning
confidence: 99%
“…The effect of asbestos exposure on lung function has been reported in several cross-sectional (10,12,(17)(18)(19) 22) and a few longitudinal (2, 11,13,20,21) studies. The latter have usually been based on two surveys.…”
mentioning
confidence: 99%